House and contents underinsurance: Insights from bushfire-prone Australia. (1st October 2022) - Booth, Kate; Lucas, Chloe; Eriksen, Christine; de Vet, Eliza; Tranter, Bruce; French, Shaun; Young, Travis; McKinnon, Scott
Abstract: As the climate changes and extreme weather events become more common, the role of house and contents insurance in managing risks is garnering more attention. There is concern, as insurance is a key safety net in contemporary life, that significant levels of house and contents underinsurance are placing individuals and communities at undue risk. Yet, the phenomenon of underinsurance is under-researched. Informed by a document analysis of findings from a multi-modal project investigating the experiences and perspectives of insured and uninsured households in bushfire-prone Australia, we identify underinsurance as a complex phenomenon that is variably co-constituted at different scales – households, landscapes, and markets. To better understand what principles can be meaningfully applied for addressing underinsurance, we present four pertinent and novel themes – place (contextualising rates of underinsurance), integration (integrating insurance with other disaster management mechanisms), hegemony (dismantling hegemonic risk discourses including reference to 'shared responsibility'), and solidarity (in insurance, and through disaster and climate responses). We conclude that addressing inequality and inequity remains paramount given the multifarious reasons why households may be underinsured. Strategies for addressing disasters and global environmental change should be socially just and inclusive irrespective of whether or not households have insurance. Highlights: In a changing climate, significant rates of house and contents underinsurance are receiving increasing attention. A multi-modal project investigated experiences of insured and uninsured households in bushfire-prone Australia. Many factors contribute to house and contents underinsurance and these vary with scale – households, landscapes and markets. Useful principles for addressing underinsurance are place, integration, hegemony, and solidarity. Addressing inequality and inequity remains paramount irrespective of whether or not households have insurance.